The Impact of Personality on Generation Y Buying Behaviour: Perception of Females on Fashion - Goi, Chai (International Association of Computer Science and Information Technology Press (IACSIT Press), 2015)
The main objective of this research is to study the impact of personality of consumers on consumer buying behaviour, especially Generation Y’s females’ buying behaviour on fashion. Five factors of personality of consumer have been applied in this study. All five factors are motivation, personal Value, personality, lifestyle and emotional. In terms of consumer buying behaviour, four factors have been applied in this study, which are psychology, socio anthropology, sociology and economic. This study shows that personality has a significant impact on their buying behaviour. Even, both factors show a significant positive correlation.